2014
DOI: 10.1177/0022022114544320
|View full text |Cite
|
Sign up to set email alerts
|

A Socio-Ecological Approach to Cross-Cultural Differences in the Sensitivity to Social Rejection

Abstract: The authors propose that cross-cultural differences in sensitivity to social rejection, or the extent to which one is alert to potential rejection from significant others, can be understood as an adaptation to different social ecological contexts varying in the degrees of relational mobility. In societies low in relational mobility, such as East Asia, relationships and group memberships are stable and exclusive, and thus it is difficult for individuals to recover once rejected from current relationships or gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 41 publications
1
72
0
3
Order By: Relevance
“…The current research brings some implications in relational mobility. Evidence supporting the significant influence of relational mobility on interpersonal relationships has been accumulating (Li et al, 2015Lou & Li, 2017;Sato et al, 2014;Schug et al, 2009Schug et al, , 2010Yamada et al, 2015). However, enemyship has not been extensively examined from the perspective of relational mobility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current research brings some implications in relational mobility. Evidence supporting the significant influence of relational mobility on interpersonal relationships has been accumulating (Li et al, 2015Lou & Li, 2017;Sato et al, 2014;Schug et al, 2009Schug et al, , 2010Yamada et al, 2015). However, enemyship has not been extensively examined from the perspective of relational mobility.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, high mobility (vs. low mobility) would promote larger friendship networks (Lun, Roth, Oishi, & Kesebir, 2012), fewer cautions about friendship and less concern about existences of enemies (Li, Adams, Kurtis, & Hamamura, 2015). Mobility also extensively shapes people's strategies used in different types of social relationships (e.g., Li, Hamamura, & Adams, 2016;Lou & Li, 2017;Sato, Yuki, & Norasakkunkit, 2014). For instance, self-disclosure in friendship (Schug, Yuki, & Maddux, 2010) and intimacy seeking in both friendship and romantic relationships (Yamada, Kito, & Yuki, 2015) are more likely to be adopted as a commitment device to strengthen relationships in high-relational-mobility societies.…”
Section: Relational Mobility and Enemyshipmentioning
confidence: 99%
“…On the other hand, low relational mobility environments are characterized by relative difficulty in forming and dissolving relationships, and there is a relative lack of opportunities for meeting new people; relationships are thus generally determined by circumstance, tend to be long standing, and be characterized by strong obligatory ties. Previous research found relational mobility to be high in North American societies, such as the United States, whereas East Asian societies, such as Japan, are low in relational mobility (Falk, Heine, Yuki, & Takemura, 2009;Schug, Yuki, Horikawa, & Takemura, 2009;Sznycer et al, 2012;Wang & Leung, 2010;Yuki et al, 2007).…”
Section: A Socio-ecological Approachmentioning
confidence: 97%
“…While most of the research reviewed here examined individualistic cultures (Peters, Eisenlohr-Moul & Smart, 2015;Velotti, Garofalo & Bizzi, 2015;Wupperman, 2006), the current study sampled a collectivist culture. In collectivist environments, relational mobility is low, which makes every relationship more valuable due to their highly stable nature (Sato, Yuki & Norasakkunkit, 2014). Accordingly, if an individual is rejected in one relationship, it is harder to become involved in a new relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, independently of personality characteristics, individuals pay a lot of attention to others' negative feedback with perceived rejection being a source of high anxiety. Thus, because individuals living in a collectivist culture may be more alert to rejection than individuals living in individualistic cultures (Garris, Ohbuchi, Oikawa & Harris, 2010;Sato, Yuki & Norasakkunkit, 2014), higher mindfulness skill levels may not be enough to reduce rejection sensitivity levels in these individuals.…”
Section: Discussionmentioning
confidence: 99%